Human Immunodeficiency Virus Type 1 (HIV-1) Vpr Enhances Expression from Unintegrated HIV-1 DNA - Poon, Betty (American Society for Microbiology, 2003)
Retroviral DNA synthesized prior to integration, termed unintegrated viral DNA, is classically believed to be transcriptionally inert and to serve only as a precursor to the transcriptionally active integrated proviral DNA form. However, it has recently been found to be expressed under some circumstances during human immunodeficiency virus type 1 (HIV-1) replication and may play a significant role in HIV-1 pathogenesis. HIV-1 Vpr is a virion-associated accessory protein that is critical for HIV-1 replication in nondividing cells and induces cell cycle arrest and apoptosis. We find that Vpr, either expressed de novo or released from virions following viral entry, is essential for unintegrated viral DNA expression. HIV-1 mutants defective for integration in either the integrase catalytic domain or the cis-acting att sites can express unintegrated viral DNA at levels similar to that of wild-type HIV-1, but only in the presence of Vpr. In the absence of Vpr, the expression of unintegrated viral DNA decreases 10- to 20-fold. Vpr does not affect the efficiency of integration from integrase-defective HIV-1. Vpr-mediated enhancement of expression from integrase-defective HIV-1 requires that the viral DNA be generated in cells through infection and is mediated via a template that declines over time. Vpr activation of expression does not require exclusive nuclear localization of Vpr nor does it correlate with Vpr-mediated cell cycle arrest. These results attribute a new function to HIV-1 Vpr and implicate Vpr as a critical component in expression from unintegrated HIV-1 DNA.